Steam explosion of crop straws improves the characteristics of biochar as a soil amendment - Xue-jiao CHEN; Qi-mei LIN; Muhammad Rizwan; Xiao-rong ZHAO; Gui-tong LI (Journal of Integrative Agriculture)
Five crop straws (wheat, rice, maize, oil-rape, and cotton) were first steam-exploded for 2 min at 210°C, 2.5 MPa and then pyrolyzed at 500°C for 2 h. Steam explosion (SE) induced 47–95% and 5–16% reduction of hemicellulose and cellulose, respectively, in the crop straws. The biochars derived from SE-treated feedstocks had a lower specific surface area (SSA) and pore volume, compared to those from pristine feedstocks, with one exception that SE enhanced SSA of oil-rape straw biochar by approximately 16 times. After SE, biochars had significant higher anion exchange capacity (AEC) (6.88–11.44 cmol kg–1) and point of zero net charges (PZNC) (pH 3.61–5.32) values. It can thus be speculated that these biochars may have higher potential for anions adsorption. In addition, oil-rape straw might be suitable to SE pretreatment for preparing biochar as a soil amendment and sorbent as well. Further work is required for testing its application in soil.